THE ROLE OF SEMIOTICS IN HUMOR TRANSMISSION AND AUDIENCE ENGAGEMENT - Горбатий, Олександр (Modern engineering and innovative technologies, 2025)
The article explores the role of semiotic mechanisms in conveying humor and engaging audiences within the digital media environment. The aim of the study is to analyze humor as a tool for audience engagement through the lens of semiotics. The research emp